Evaluating Serum Uric Acid as a Predictive Marker for Outcomes in Pediatric Acute Lymphoblastic Leukemia - Abid Ali Ranjha, Nasir Khan, Tabassum Bashir, Mandeep Kumar, Zahra Riaz, Azal Jodat, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
A prospective cohort of 150 children aged 2–16 years newly diagnosed with acute lymphoblasticleukemia (ALL) was followed to assess the prognostic role of baseline serum uric acid (SUA)levels in treatment response, early tumor lysis syndrome (TLS), and survival outcomes. BaselineSUA was measured prior to induction therapy.